Prevalence of Babesia species and associated ticks (Acari : Ixodidae) in captive cheetah (Acinonyx jubatus) populations in South Africa - Penzhorn, Barend Louis (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2011.